PATHOCRINIA. ETIOLOGY AND PATHOGENESIS: ADRENAL ABNORMALITIES - P.F. Litvitskiy (Вопросы современной педиатрии, 2011)
This lecture is dedicated to the causes and key features of pathogenesis of adrenal hyper- and hypofunction, their clinical presentations and pathogenesis; specific nosologies, caused by adrenal abnormality. One can also find tests and clinical cases attached to the lecture, along with answers. Key words: hyperaldosteronism, hypoaldosteronism, corticogenital syndrome, pheochromocytoma, addisonian crisis. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 63–73.)